Understanding charateristics of the malay cultural landscape through pantun, woodcarving and old literature - Ismail, Nor Atiah; Mohd. Ariffin, Noor Fazamimah; Ismail, Sumarni; Mohd Yunus, Mohd. Yazid; Nangkula, Utaberta (American-Eurasian Network for Scientific Information Publications(AENSI), 2015)
Background: The Malays traditionally and especially before the arrival of Islam were animistic in their belief. Their lives were closely inter-twinned with nature for sustenance as well as for the spiritual and emotional comfort. They respect the natural world of the seen as well as the unseen. With the advent of Islam most of the animistic beliefs of the Malays have been discarded. However, the awe that the Malays have toward the forest or the river, the sea or the mountain is still a reminiscence of their ancestral beliefs. These beliefs have helped them survive the hostile environment they had evolved from and acquire a great deal of knowledge and understanding about their natural surrounding which has been handed down from generation to generation. Objectives: This paper suggests an understanding of the characteristics of the Malay cultural landscape through pantun, woodcarving and old literature Results: The Malay Pantun, Malay Woodcarvings and the literature in Bustan Al-Salatin are analyzed in the process of understanding an authentic values of the Malay cultural landscape. Conclusion: The Malay cultural landscape is unique and always been used by the traditional community and an inspiration for art and crafts. It is indeed, a recorded evident for the current generation to understand our heritage and cultural values.